The Relationship between Brand Personality and Brand Loyalty: An Empirical Literature Review - Haryaji Catur Putera Hasman, (Journal Business Administration: Entrepreneurship and Creative Industry, 2025)
This study aims to examine the relationship between brand personality and brand loyalty based on empirical research published in the last five years. The review was conducted using a focused narrative literature review approach, analyzing ten scholarly articles obtained from accredited national and international journals. Inclusion criteria included articles published between 2019 and 2024, empirical studies based on primary data, full-text availability, and a clear focus on the relationship between brand personality and brand loyalty. The findings reveal that, in general, brand personality has a positive influence on brand loyalty, either directly or indirectly through mediating variables such as brand trust, brand satisfaction, brand equity, self-congruity, and customer brand identification. Several brand personality dimensions, such as sincerity, competence, and ruggedness, were found to have a stronger effect on brand loyalty compared to other dimensions. These results highlight the strategic importance of brand personality management in fostering customer loyalty. This review is expected to serve as a conceptual reference for researchers and marketing practitioners in understanding the dynamics between brand character and consumer loyalty in an increasingly competitive brand landscape.